Effects of abscisic acid and gibberellin on sugar accumulation in 'Fengtang' Plum (Prunus salicina LindI.) - Qianjun Song; Xiaoshuang Nie; Hong Chen (Horticultural Science)
To investigate the regulation mechanism of exogenous plant growth regulators on the sugar accumulation of 'Fengtang' plum fruits, and to provide theoretical support for improving the sugar content of 'Fengtang' plum fruits. The expression of fruit sugar fractions and related genes was determined by spraying different concentrations of exogenous  abscisic acid (ABA) and Gibberellic acid 3 (GA3) during the critical period of sugar accumulation in 'Fengtang' plum. The results showed that exogenous ABA treatment increased fruit soluble solids content, delayed the decline in fruit firmness, increased fruit sucrose and sorbitol content and decreased glucose and fructose content at 90 and 100 days after flowering, while exogenous GA3 treatment decreased fruit sorbitol and sucrose content and increased glucose and fructose content at 110 days after flowering; Exogenous ABA treatment significantly increased the expression of the fruit sugar transporter protein genes PsSWEET4 and PsSTP1 as well as the sucrose phosphate synthase genes PsSUS4 and PsSPS2 at 90 and 100 days after flowering, whereas exogenous GA3 treatment increased the expression of the neutral converting enzyme genes PsNINV1/3/4 at 90, 100, and 110 days after flowering to convert sucrose to fructose and glucose. The conclusion is that ABA increases fruit sugar content by increasing the expression of the fruit sugar transporter protein genes PsSWEET4 and PsSTP1 as well as the sucrose synthase genes PsSUS4 and PsSPS2, whereas GA3 decreases sugar accumulation and delays fruit ripening by decreasing the accumulation of sugar during ripening by increasing the expression of the neutral transforming enzyme genes PsNINV1/3/4 to break down sucrose into fructose and glucose.